Business Analytics Using R - A Practical Approach [electronic resource] - Hodeghatta, Umesh R.; Nayak, Umesh; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2017)
Learn the fundamental aspects of the business statistics, data mining, and machine learning techniques required to understand the huge amount of data generated by your organization. This book explains practical business analytics through examples, covers the steps involved in using it correctly, and shows you the context in which a particular technique does not make sense. Further, Practical Business Analytics using R helps you understand specific issues faced by organizations and how the solutions to these issues can be facilitated by business analytics. This book will discuss and explore the following through examples and case studies: An introduction to R: data management and R functions The architecture, framework, and life cycle of a business analytics project Descriptive analytics using R: descriptive statistics and data cleaning Data mining: classification, association rules, and clustering Predictive analytics: simple regression, multiple regression, and logistic regression This book includes case studies on important business analytic techniques, such as classification, association, clustering, and regression. The R language is the statistical tool used to demonstrate the concepts throughout the book. You will: ? Write R programs to handle data ? Build analytical models and draw useful inferences from them ? Discover the basic concepts of data mining and machine learning ? Carry out predictive modeling ? Define a business issue as an analytical problem.
Keywords: Computer science; Computer programming; Programming languages (Electronic computers).; Mathematical statistics; Data mining; Information storage and retrieval; Computer Science; Big Data; Programming Techniques; Programming Languages, Compilers, Interpreters; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Probability and Statistics in Computer Science